Validation of Indonesian Graves’ Ophthalmopathy Quality of Life Questionnaire and Its Association with Clinical Activity and Severity of Graves’ Ophthalmopathy - Cecilia Anggraini; Syntia Nusanti; Dicky Levenus Tahapary; Levina Chandra Khoe (Acta Medica Indonesiana)
Background: Graves’ ophthalmopathy (GO) ocular abnormalities can persist even after treatment, negatively impacting patients’ psychological and social health. The Indonesian Graves’ Ophthalmopathy Quality of Life (GO-QoL) Questionnaire has not been validated, hence it cannot measure patient quality of life, which is crucial to GO treatment. We aimed to provide a reliable Indonesian GO-QoL Questionnaire and identify an association between patient quality of life and clinical activity and the severity of GO. Methods: The process of questionnaire validation involves transcultural adaptation and a cross-sectional design. The content validity index (CVI) and Cronbach’s alpha assessed validity and reliability, respectively. Results: The CVI was 1.00 for the Indonesian GO-QoL questionnaire. The Cronbach’s alpha for the visual function subscale value was 0.971, the appearance subscale value was 0.993, and the total score was 0.986. The appearance subscale and total score of GO patients’ quality of life had a significant association with clinical activity score (p<0.05) and disease severity (p<0.001). Conclusion: The Indonesian version of the GO-QoL has good validity and reliability. Both the active clinical activity of GO and the severity of the disease decreased patients’ appearance and general quality of life.